1999
DOI: 10.1023/a:1007084506071
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Heteropolysaccarides were isolated from the Korean medicinal plant, Phellodendri cortex (Hwangbek), by hot water and alkali extractions. The extracted polysaccharides were fractionated into eight fractions and they are mainly composed of D-N-acetylglucosamine, D-galactose, D-mannose, and D-glucose. Among the polysaccharide fractions, Fr.-2 showed a potent B-lymphocyte-stimulating activity in a system using polyclonal antibody forming cells in C57BL/6XC3H mice at dosages of 2-10 mg. On the basis of their solubi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…23 HHT exerts prominent effect in improving immune function in animal models and patients with immune dysfunction by activating various immune cell types, including macrophages and NK cells, which regulate the expression of immune-related cytokines. 24,25 HHT comprises four herbal medicines: Rhizoma coptidis, Radix scutellariae, Cortex phellodendri, and Fructus gardenia. 26 The active ingredients of HHT consist of total alkaloids, total flavonoids, and total iridoid.…”
Section: Introductionmentioning
confidence: 99%
“…23 HHT exerts prominent effect in improving immune function in animal models and patients with immune dysfunction by activating various immune cell types, including macrophages and NK cells, which regulate the expression of immune-related cytokines. 24,25 HHT comprises four herbal medicines: Rhizoma coptidis, Radix scutellariae, Cortex phellodendri, and Fructus gardenia. 26 The active ingredients of HHT consist of total alkaloids, total flavonoids, and total iridoid.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, it was used to clear heat, dry dampness, purge free, and remove toxicity [ 2 ]. Besides, modern pharmacological research studies indicated that Phellodendri Cortex exhibited various pharmacological activities, such as relaxing airway smooth muscle [ 2 ], inhibiting diabetes and gout [ 3 ], antioxidant [ 4 ], anti-inflammation [ 5 7 ], antiulcer [ 8 ], antibacteria, neuroprotective [ 9 ], antiviral, antidiarrhea [ 10 ], bone growth-stimulation, and immune-stimulation activities [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, Phellodendri Cortex polysaccharides (CPP) exhibited potent antitumor activity against sarcoma [ 24 ]. The CPP fraction showed marked B-lymphocyte-stimulating activity [ 11 ]. However, few studies were conducted to evaluate immunoenhancement activity of CPP under immunosuppression.…”
Section: Introductionmentioning
confidence: 99%
“…It is one of fundamental traditional Chinese medicines. Previous study reported that C. phellodendri has many physiological activities, including antioxidant [ 2 , 3 ], anti-inflammatory [ 4 6 ], antiulcer [ 7 ], and immune-stimulating properties [ 8 ], as well as neuroprotection and inhibition of coronavirus replication [ 9 , 10 ]. Moreover, C. phellodendri combining with other herbs can reduce complications of corticosteroid-resistant asthma [ 11 ].…”
Section: Introductionmentioning
confidence: 99%